Automated evaluation and normalization of immunohistochemistry on tissue microarrays with a DNA microarray scanner - Wolfgang Haedicke; Helmut H. Popper; Charles R. Buck; Kurt Zatloukal (BioTechniques)
Hundreds of tissue samples may be assembled in a tissue microarray format for simultaneous immunostaining assessment of protein expression profiling. A DNA microarray two-color laser scanner was used for automated analysis of tissue microarray indirect immunofluorescence. On sections from both a human lung adenocarcinoma and a squamous cell carcinoma tissue microarray, fluorescence intensity for two epidermal growth factor receptors (EGFR and c-erbB2) correlates with diagnostic pathologist assessment, indicating that immunohistochemistry quantitation can be achieved. Importantly, double-label indirect immunofluorescence detection with the cDNA scanner demonstrates that one reference antigen can normalize tumor marker immunosignal for the cellular content of tissue microarray tissue cores. Therefore, DNA microarray scanners and associated image analysis software provide general and efficient analysis of tissue microarray immunostaining, including estimation of specific protein expression levels.